CPAL, as a New Mediator of Cardiomyocyte Metabolic Alterations and Pyroptosis, Regulates Myocardial Infarction Injury in Mice. (January 2023) - Li, Jiamin; Xue, Hongru; Xu, Ning; Gong, Liling; Li, Ming; Li, Sijia; Huang, Di; Zhang, Qingwei; Li, Pengyu; Li, Qingsui; Yu, Hang; Liu, Yining; et al.
Graphical abstract: Abstract: Myocardial infarction (MI), the most serious of the ischemic heart diseases, is accompanied by myocardial metabolic disorders and the loss of cardiomyocytes. Increasing evidence has shown that long noncoding RNAs (lncRNAs) are involved in various pathological conditions such as cancer and cardiovascular diseases (CVDs), and are emerging as a novel biomarker for these disorders. This study aims to investigate the regulatory role and mechanisms of lncRNAs in myocardial remodeling in the setting of MI. We find that post-infarcted hearts exhibit a reduction of adenosine triphosphate (ATP) and an alteration of the glucose and lipid metabolism genes cluster of differentiation 36 (CD36), hexokinase 1 ( HK1 ), and clucose transporter 4 ( GLUT 4), accompanied by cardiomyocyte pyroptosis. We then identify a previously unknown conserved lncRNA, AK009126 (cardiomyocyte pyroptosis-associated lncRNA, CPAL), which is remarkably upregulated in the myocardial border zone of MI mice. Importantly, the adeno-associated virus 9 (AAV9)-mediated silencing of endogenous CPAL by its short hairpin RNA (shRNA) partially abrogates myocardial metabolic alterations and cardiomyocyte pyroptosis during MI in mice. Mechanistically, CPAL is shown to bind directly to nuclear factor kappa B (NFκB) and to act as an activator of NFκB to induce NFκB phosphorylation in cardiomyocytes. We also find that CPAL upregulates caspase-1 expression at the transcriptional level and consequently promotes the release of interleukin (IL)-18 and IL-1β from cardiomyocytes. Collectively, our findings reveal the conserved lncRNA CPAL as a new regulator of cardiac metabolic abnormalities and cardiomyocyte pyroptosis in the setting of MI and suggest CPAL as a new therapeutic target to protect cardiomyocytes against ischemic injury in infarcted hearts.